Zooplankton diversity across three Red Sea reefs using pyrosequencing - Pearman, John K.; El-Sherbiny, Mohsen M.; Lanzén, Anders; Al-Aidaroos, Ali M.; Irigoien, Xabier (Frontiers in Marine Science, 2014)
Coral reefs are considered among the most diverse ecosystems on Earth, yet little is known about the diversity of plankton in the surrounding water column. Moreover, few studies have utilised genomic methods to investigate zooplankton diversity in any habitat. This study investigated the diversity of taxa by sampling 45 stations around three reef systems in the central/southern Red Sea. The diversity of metazoan plankton was investigated by targeting the 18S rRNA gene and clustering OTUs at 97% sequence similarity. A total of 754 and 854 metazoan OTUs were observed in the data set for the 1380F and 1389F primer sets respectively. The phylum Arthropoda dominated both primer sets accounting for ~60% of reads followed by Cnidaria (~ 20%). Only about 20% of OTUs were shared between all three reef systems and the relation between geographic distance and Jaccard Similarity measures was not significant. Cluster analysis showed that there was no distinct split between reefs and stations from different reefs clustered together both for metazoans as a whole and for the phyla Arthropoda, Cnidaria and Chordata separately. This suggests that distance may not be a determining factor in the taxonomic composition of stations.